Megalopolis: The Giant City in History
XI, 213 p.
Keywords: This book follows the evolution of the very large city across the world from its origins in Ancient times to its current dominant position in both the industrialised world and the Third World. In-depth studies are devoted to the key giant cities of human history at decisive points in their growth. The case-studies include Rome, London, Saint-Petersburg, Moscow, Bangkok and Berlin. Additional studies deal with the general characteristics of the megalopolis, stressing its implications for cultural life.